2022
DOI: 10.1136/bcr-2022-253250
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin toxicity

Abstract: Provenance and peer review Not commissioned; externally peer reviewed.Case reports provide a valuable learning resource for the scientific community and can indicate areas of interest for future research. They should not be used in isolation to guide treatment choices or public health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The results indicated that lower detection limits were achieved by TD-ESI/MS/MS than those of TD-ESI/MS for the detection of adulterant standards prepared in methanol and of those spiked in different herbal preparations (Table 4). Human serum >20 μg/mL acetaminophen, 49 >15 μg/mL caffeine, 50 > 1.5 μg/mL diazepam, 51 > 20 μg/mL phenytoin, 52 and >45 μg/mL phenylbutazone. 53 Such over- dose levels encountered in actual clinical practice are far higher than the LODs of TD-ESI/MS described in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that lower detection limits were achieved by TD-ESI/MS/MS than those of TD-ESI/MS for the detection of adulterant standards prepared in methanol and of those spiked in different herbal preparations (Table 4). Human serum >20 μg/mL acetaminophen, 49 >15 μg/mL caffeine, 50 > 1.5 μg/mL diazepam, 51 > 20 μg/mL phenytoin, 52 and >45 μg/mL phenylbutazone. 53 Such over- dose levels encountered in actual clinical practice are far higher than the LODs of TD-ESI/MS described in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Phenytoin has a narrow therapeutic margin and should be closely monitored. The primary concern and unpredictable scenario is when patients develop toxicity despite usual therapeutic doses (200–400 mg/day) [ 3 ]. The drug follows a nonlinear pharmacokinetic profile.…”
Section: Introductionmentioning
confidence: 99%